Altitudinal distribution limit of the tick Ixodes ricinus shifted considerably towards higher altitudes in central Europe: results of three years monitoring in the Krkonose Mts. (Czech Republic) - Materna, J; Daniel, M; Danielová, V (Central European journal of public health, 2005)
The aim of the study was to monitor present status of the Ixodes ricinus tick vertical distribution in the Krkonose Mts. (Czech Republic) and evaluate its potential changes. Two methods were used: monitoring of tick presence on dogs in 2001-2002 and direct monitoring of host-seeking ticks by flagging on two vertical transects reaching from 620 to 1270 m above sea level (a. s. l.) and from 600 to 1020 m in 2002-2003. Moreover ticks were monitored by flagging at another 13 localities situated in 800-1299 m a. s. l. in 2003. Both monitoring methods revealed an obvious shift in altitudinal distribution limit of the tick I. ricinus in the Krkonose Mts. They both showed that ticks recently penetrate even up to a timberline (approximately 1250 m a. s. l.). The number of recorded host-seeking ticks rapidly decreased with increasing altitude. Whereas the average number of recorded nymphs converted per 60 minutes of flagging reached 15.2-25.7 nymphs in 700-799 m a. s. l. and 3.3-23.3 in 800-899 m, it was 4-9.6 nymphs in 900-999 m, 1.5-1.7 nymphs in 1000-1099 m and only 0.2 nymph in 1100-1299 m a. s. l. The observed shift of the tick altitudinal distribution limit at the same time results in extension of areas with potential risk of tick-borne diseases.
Keywords: Environmental Monitoring; psi; Ixodes; monitorování životního prostředí; klíště; Cats; Animals; kočky; Česká republika; Dogs; Altitude; Czech Republic; zvířata; nadmořská výška